Regulation of endothelial hemoglobin alpha expression by Kruppel-like factors. (October 2017) - Sangwung, Panjamaporn; Zhou, Guangjin; Lu, Yuan; Liao, Xudong; Wang, Benlian; Mutchler, Stephanie M; Miller, Megan; Chance, Mark R; Straub, Adam C; Jain, Mukesh K
Hemoglobin subunit alpha (HBA) expression in endothelial cells (ECs) has recently been shown to control vascular tone and function. We sought to elucidate the transcriptional regulation of HBA expression in the EC. Gain of KLF2 or KLF4 function studies led to significant induction of HBA in ECs. An opposite effect was observed in ECs isolated from animals with endothelial-specific ablation of Klf2, Klf4 or both. Promoter reporter assays demonstrated that KLF2/KLF4 transactivated the hemoglobin alpha promoter, an effect that was abrogated following mutation of all four putative KLF-binding sites. Fine promoter mutational studies localized three out of four KLF-binding sites (sites 2, 3, and 4) as critical for the transactivation of the HBA promoter by KLF2/KLF4. Chromatin immunoprecipitation studies showed that KLF4 bound to the HBA promoter in ECs. Thus, KLF2 and KLF4 serve as important regulators that promote HBA expression in the endothelium.